2011
DOI: 10.1111/j.1399-0039.2011.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

KIR/HLA gene combinations influence susceptibility to B‐cell chronic lymphocytic leukemia and the clinical course of disease

Abstract: The aim of this study was to analyze the association between gene polymorphisms of killer-cell immunoglobulin-like receptors (KIRs) and their human leukocyte antigen (HLA) ligands and susceptibility to B-cell chronic lymphocytic leukemia (B-CLL) and the clinical course of disease. The distribution of individual KIR genes in 197 B-CLL patients and 200 controls was similar, except for a tendency for lower frequencies of the KIR2DS3 and KIR2DL5 genes among B-CLL patients (26.9% vs 35.5%, P = 0.06, 46.2% vs 55.5%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
1
26
0
2
Order By: Relevance
“…[35][36][37] Since all our 2DS3-positive patients presented also 2DS2, we compared ADCC levels in this combined cohort with 2DS2-positive patients missing 2DS3. Importantly, we did not detect a difference in ADCC levels and EFS between patients with only 2DS2 compared to 2DS2-and 2DS3-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Since all our 2DS3-positive patients presented also 2DS2, we compared ADCC levels in this combined cohort with 2DS2-positive patients missing 2DS3. Importantly, we did not detect a difference in ADCC levels and EFS between patients with only 2DS2 compared to 2DS2-and 2DS3-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 Notably, autoantigen-specific cytotoxic CD8 + T cells expressing inhibitory KIRs have been isolated from human blood. [21][22][23] It is therefore conceivable that KIR-mediated inhibitory signals such as those provided by KIR2DL3 regulate NK-and T-cell activation during autoimmune responses in MS. 5,24,25 We observed that individuals carrying two copies for KIR2DL2 but lacking KIR2DL3 were overrepresented in the CIS/MS cohort. Similarly, the frequency of KIR2DL3-negative donors homozygous for KIRD2DS2, with which KIR2DL2 shares strong linkage disequilibrium, was significantly higher in the CIS/MS cohort.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have revealed that coexpression of KIR and particular HLA ligands are associated with leukemia [17][18][19], but rare data was reported in Chinese population. So we compared the distribution of KIR3DS1 and HLA-Bw4 ligands in AML individuals with healthy individuals to investigate the association of 3DS1 gene and HLA-Bw4 with AML.…”
Section: Discussionmentioning
confidence: 91%
“…It is widely accepted that KIRs, especially the specific KIR-ligand combination, may have associations with leukemia [3,[17][18][19]. KIRD3S1 is one of the main activating molecules which has been conserved during the last several million years.…”
Section: Discussionmentioning
confidence: 99%